Objectively Assessed Daily Steps—Not Light Intensity Physical Activity, Moderate-to-Vigorous Physical Activity and Sedentary Time—Is Associated With Cardiorespiratory Fitness in Patients With Schizophrenia - Engh, John A.; Egeland, Jens; Andreassen, Ole A.; Bang-Kittilsen, Gry; Bigseth, Therese T.; Holmen, Tom L.; Martinsen, Egil W.; Mordal, Jon; Andersen, Eivind (Frontiers in Psychiatry, 2019)
People with schizophrenia often have an unhealthy sedentary lifestyle with low level of physical activity and poor cardiorespiratory fitness - an important predictor of cardiovascular disease. We investigated the relations between cardiorespiratory fitness and both sedentary time and different aspects of physical activity, such as daily steps, light intensity physical activity, and moderate-to-vigorous physical activity. Using accelerometer as an objective measure of sedentary time and physical activity we estimated their relations to cardiorespiratory fitness in sixty-two patients with schizophrenia with roughly equal gender distribution, mean age of 36 and 15 years illness duration. We found a significant association between daily steps and cardiorespiratory fitness when accounting for gender, age, sedentary time, light intensity physical activity and respiratory exchange ratio (maximal effort). Moderate-to-vigorous physical activity was not significantly associated with cardiorespiratory fitness. In conclusion, the amount of steps throughout the day contributes to cardiorespiratory fitness in people with schizophrenia, independently of light intensity physical activity and sedentary time. We did not find a significant relationship between moderate-to-vigorous physical activity and cardiorespiratory fitness. This may have implications for the choice of strategies when helping patients with schizophrenia improve their cardiorespiratory fitness.